ANN Validation of Biodiesel Synthesis Optimization using Heterogeneous Catalyst (SiO2) - Satish A. Patil; R. R. Arakerimath (Recent Developments in Engineering Research Vol. 12, 2021)
Biodiesel is a renewable, ecofriendly fuel that can provide comparable engine performance. Karanja oil is made in this experiment using a transesterification process with SiO2 as a heterogeneous catalyst. It is investigated utilising five separate parameters and their respective levels. The orthogonal arrays are fixed using Minitab, and the Taguchi method is utilised to study the interaction impact for the transesterification reaction. Molar ratio, catalyst concentration, reaction temperature, reaction time, and stirring speed are the five variables that affect biodiesel yield. The impact of these variables has been investigated on a limited scale. Experimentally biodiesel yield obtained is 77% at optimum conditions are 20% molar ratio, 3% SiO2 catalyst addition, 65ºC reaction temperature, 180 min reaction time and 500 rpm stirring speed. Minitab results are compared here with ANN results using script by analytically as well as graphically.